Answer:
3(u +5) - 7u=-4u +15
Step-by-step explanation:
According to the given data we have the following expression:
3(u +5) - 7u
To simplify this we would make the following:
First we would expand 3(u+5) applying the distributive law:
distributive law:
![a\mleft(b+c\mright)=ab+ac](https://img.qammunity.org/2023/formulas/mathematics/college/ar19g5md1rdfruc182uilayeoqqpubcrsx.png)
![a=3,\: b=u,\: c=5.\text{ So, }3\mleft(u+5\mright)=3u+15](https://img.qammunity.org/2023/formulas/mathematics/college/crf3nv7q3v7m9i40l7a2oipwkxs1kf3biz.png)
So, 3u + 15 -7u=0
Finally simplify 3u + 15 -7u, so you would add the similar elements.
Therefore, you would get -4u +15